A survey of worker participation in Bophuthatswana - Lewis, David (Organisational Psychology, 2023)
Worker participation and the acceptance thereof is well established in first world countries. In third world countries it is still a relatively new concept which tends to rely on legislation for its existence and continuing function. Where a free-market economy is in place, labour market forces and management attitudes tend to affect the practice of worker participation. This research explores the multi-dimensional nature of workers' attitudes towards worker participation in an international company operating in the Republic of Bophuthatswana. A questionnaire using the hypothetical conversation technique and a dichotomous scale was developed and administered to a sample of 300 male industrial workers. Ten dimensions were proposed and subjected to a factor analysis. The results of the factor analysis revealed a unidimensional scale which suggested an underlying general attitude. This was used as a "general attitude" scale. Only two of the original dimensions were found to have some factorial validity. These three scales were subjected to an item analysis to establish their internal consistency. The biographical data in the questionnaire and the three scales were subjected to a correlation study and a regressional analysis to determine what relationship existed between the biographical variables and the attitudinal scales. This was done to explore the three scales. It was found that only tenure affected all three scales; tenure and not age was the variable that affected workers' attitudes the most.